PENDAPATAN ASLI DAERAH DARI SEKTOR PAJAK DALAM RANGKA PELAKSANAAN OTONOMI DAERAH - Lies Ariany (Masalah-Masalah Hukum, 2010)
The regional tax was the source income the areal that important to finance the implementation of autonomy of the area. Then area must have the authority and the capacity to dig up sources of finance self, manage and used finance personally that really adequate to finance the implementation of the government. But each government stage could only collect the tax that was mainteed to authority. It's mean to avoid the existence of the overlap or the struggle for the authority in the tax collection againts the community.Kata Kunci : Pajak Daerah, Pendapatan Asli Daerah